Methods of selection for chilling tolerance in Nepalese rice by chlorophyll fluorescence analysis - Sthapit, B.R. (Lumle Agric. Res. Centre, Pokhara, Nepal.); Witcombe, J.R; Wilson, J.M (Crop science, 1995)
Rice (Oryza sativa L.) yields are frequently low in the high hills of Nepal because of chilling temperatures throughout the growing season. Conventional screening for chilling sensitivity of different rice genotypes in breeding programs relies on visual observations in the field. The screening is subjective, time consuming, and subject to genotype X environment, interactions (e.g., stage of development when chilled). In this study, chlorophyll fluorescence analysis (CFA) was used to test its value in assessing chilling tolerance. Landraces and cultivars with known chilling sensitivities, including chilling-tolerant landraces and cultivars from Nepal, were compared. Detached leaves from plants of 16 rice genotypes at the tillering stage were chilled in growth cabinets before their photochemical efficiencies (Fv/Fm) were measured by CFA. Genotype differences were examined by three methods: absolute Fv/Fm ratios of excised leaves chilled for 24 to 72 h at 10 degrees C, decline in Fv/Fm ratios of excised leaves chilled for 24 to 72 h at 10 degrees C in comparison to unchilled checks, and absolute Fv/Fm ratios of chilled leaves after recovery of up to 72 h at 25 degrees C in the dark. Altitudes of the site of genotype adaptation correlated well with Fv/Fm ratios after chilling for 48 h, whether Fv/Fm, values were the absolute values or percentages of corresponding unchilled checks. The absolute Fv/Fm ratios of the chilled plants after 48 h recovery at 25 degrees C gave the highest correlation with altitude but that correlation was not significantly better than the correlation obtained with the absolute Fv/Fm ratios determined in the absence of a recovery period